The perspective of Qur’an on other world religions - Shehu, Fatmir Mehdi (2015)
The world religions have been addressed by many intellectuals and scholars from different approaches, such as philosophical, anthropological, phenomenological, sociological, psychological, religious, and so on, where the very essence of religion(s) has been speculated, vilified and distorted. The reading of religions from such approaches, which are human endeavour and not Divine, has formed a kind of confusion and misunderstanding in the mind of many people especially the young generation. A unique perspective on world religions and traditions cannot be addressed by referring to the work of man. Rather, it requires an accurate, authentic and comprehensive source of knowledge, which is Divine in Nature, such as the Holy Qur’an. The main thrust of this paper will be on the perspective of Qur’an on other world religions and traditions. This paper will discuss the unique approach of Qur’an on (1) Din of Allah (s.w.t.), al-Islam and its distinction from other world religions and traditions; (2) the classification of world religions and traditions based on their authenticity with the Truth – Idol Worshipers (the Arab Pagans), Ahl al-Kitab (Jews and Christians), the Sabians and the Magians; and (3) the major themes with regard to other religions and traditions, such as kutub and suhuf (scriptures and texts), aqidah and iman (creed and faith), and ibadah and shariah (worship and law); and (4) the techniques that Muslims should use in their relationship with followers of other world religions and traditions. Descriptive, analytical and comparative methods will be employed by the researcher throughout this paper. This study is very important as it attempts to provide very significant findings and suggestions that will very beneficial for the young scholars in the field of comparative religion.